Pearl Sac Gene Expression Profiles Associated With Pearl Attributes in the Silver-Lip Pearl Oyster, Pinctada maxima - McDougall, Carmel; Aguilera, Felipe; Shokoohmand, Ali; Moase, Patrick; Degnan, Bernard M. (Frontiers in Genetics, 2021)
Pearls are highly prized biomineralised gemstones produced by molluscs. The appearance and mineralogy of cultured pearls can vary markedly, greatly affecting their commercial value. To begin to understand the role of pearl sacs - organs that form in host oysters from explanted mantle tissues that surround and synthesise pearls - we undertook transcriptomic analyses to identify genes that are differentially expressed in sacs producing pearls with different surface and structural characteristics. Our results indicate that gene expression profiles correlate with different pearl defects, suggesting that gene regulation in the pearl sac contributes to pearl appearance and quality. For instance, pearl sacs that produced pearls with surface non-lustrous calcification significantly down-regulate genes associated with cilia and microtubule function compared to pearl sacs giving rise to lustrous pearls. These results suggest that gene expression profiling can advance our understanding of processes that control biomineralisation, which may be of direct value to the pearl industry, particularly in relation to defects that result in low value pearls.